Systematic Literature Review: Analisis Hambatan Belajar Siswa dalam Materi Matematika SMP - Oktavihari, Dita; Kertiyani, Ni Made Intan (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Difficulties in learning can be one of the factors that cause learning obstacles. Learning obstacles can interfere with students' learning process internally and externally. This study aims to analyze learning obstacles that arise at the junior high school level to be the basis for making further designs. The research methodology used is a systematic literature review by collecting articles related to learning obstacles at the junior high school level. The data analysis technique used is data extraction. The data obtained were 15 articles related to learning obstacles in mathematics material at the junior high school level in the 2021-2024 period. The results obtained were ontogenic barriers, epistemological barriers, and didactic barriers. The ontogenic barriers obtained were students' unpreparedness during learning, lack of interest and motivation to learn, and lack of understanding of prerequisite material. The epistemological barriers obtained were misconceptions, unable to understand, identify, and analyze problems, inaccuracy, and limitations in solving the questions given. The didactic barriers obtained were teacher-centered learning, fast learning rhythm, inappropriate teaching material arrangements, and inadequate school facilities. Based on the obstacles obtained, a learning flow can be designed, and a didactic design can be developed to minimize the emergence of these learning obstacles.